PTH-158 The presence of perineural, blood and lymphvessel invasion after neoadjuvant therapy and oesophagectomy identifies high risk patients for recurrence. (22nd June 2015) - Lagarde, SM; Navidi, M; Phillips, AW; Disep, B; Immanuel, A; Griffin, M
Abstract : Introduction: In patients with oesophageal cancer, little attention has been paid to the relevance of tumour invasion in blood (AI) and lymphatic vessels (LVI) as well as perineural invasion (PNI) after neoadjuvant therapy. Therefore, the aim of the present study was to assess the incidence and prognostic significance of these factors in a consecutive series of patients with cancer of the oesophagus or gastro-oesophageal junction (GOJ) who underwent neoadjuvant therapy followed by oesophagectomy. Method: From a prospectively collected database, a consecutive series of patients was analysed. All patients with potentially curable adeno- or squamous cell carcinoma of the oesophagus or GOJ were treated with neoadjuvant chemotherapy or chemoradiation therapy followed by transthoracic oesophagectomy and two-field lymphadenectomy. The presence of AI, LVI and PNI was prospectively collected. Results: Between January 2000 and September 2013, a consecutive series of 396 patients underwent a potentially curative oesophagectomy after neoadjuvant therapy for adeno- or squamous cell carcinoma. AI was seen in 150 (38%) of patients, LVI was seen in 203 (51%) of patients and PNI was seen in 204 (52%) of patients. 123 (31%) had no AI, LVI or PNI whatsoever. 96 (24%) had a combination of two out of three factors and 94 (24%) had presence of AI, LVI and PNI. The presence of AI, LVI and PNI was significantly (P = 0.001) related with ypT- and ypN-stage. Median overall survival was 170.8 months (95% CI: 68.9–272.8) if AI, LVI and PNI were all absent, 44.0 months (95% CI: 20.9–67.2) when one factor was present, 27.1 months (95% CI: 22.8–31.4) when two factors were present and 16.0 months (95% CI: 9.4–22.6) when AI, LVI and PNI were all present. On multivariate analyses the presence of AI, LVI and PNI or a combination of these factors were independent predictors. Conclusion: These findings suggest the importance of the presence of AI, LVI and PNI after neoadjuvant therapy followed by oesophagectomy. The presence of AI, LVI and PNI should be incorporated in the standardised pathology report. It provides additional information for identyfying patients at high risk who may be candidates for adjuvant therapies. Disclosure of interest: None Declared.